2023
DOI: 10.3390/ijerph20043050
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Work from Home and Musculoskeletal Discomfort: An Investigation of Ergonomic Factors in Work Arrangements and Home Workstation Setups Using the COVID-19 Experience

Abstract: The COVID-19 pandemic provided an opportunity for office workers to experience work from home (WFH). The aims of this study are to investigate the prevalence rate of musculoskeletal discomfort (MSD) and the work conditions of homeworkers during WFH as well as to evaluate the association and predicted risk of ergonomic factors and MSD. A total of 232 homeworkers completed questionnaires. Chi-square test and logistic regression were used to analyze the association and prediction of work arrangements and home wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Various studies have examined the extent to which working from home has an impact on the prevalence of musculoskeletal complaints. In particular, back and neck pain depends on the office chairs and monitors used, and these conditions are likely to be suboptimal in the home office in most cases (Chim and Chen 2023 ). In addition, a study on university students who were required to attend online classes during the pandemic found that of 1450 students surveyed, 42.8% suffered from mild/moderate dry eye symptoms and 34.7% suffered from severe symptoms (Cartes et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have examined the extent to which working from home has an impact on the prevalence of musculoskeletal complaints. In particular, back and neck pain depends on the office chairs and monitors used, and these conditions are likely to be suboptimal in the home office in most cases (Chim and Chen 2023 ). In addition, a study on university students who were required to attend online classes during the pandemic found that of 1450 students surveyed, 42.8% suffered from mild/moderate dry eye symptoms and 34.7% suffered from severe symptoms (Cartes et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uncorrected standing left profile ID. 3 Corrected standing en face ID. 4 Corrected standing left profile ID.…”
Section: Appendix a Dataset File Formatsmentioning
confidence: 99%
“…The primary reason for MSDs, chronic back or neck pain, and other chronic pain conditions is improper sitting positions for prolonged hours. The improper sitting positions are most often due to the non-ergonomic environment set by the old-fashioned paradigm, which forces computer users to adapt to ad hoc computer tables/desks at home or in the office [3,4]. Even well-informed computer users and professional software developers who are working in an ergonomic environment (including office chairs, desks, keyboards, mice, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Parents with lower wages were expected to lose their jobs more and were less likely to work from home than parents who had middle or high wages. However, working from home caused musculoskeletal problems for a large percentage of employees [76]. Similarly, Bentley et al [77], through quantitative research, engaged in the development of an occupational health and safety management model for employees who were working from home in Australia.…”
Section: Health Issuesmentioning
confidence: 99%